Examination of recreational service quality with different variables: an application on individuals who do outdoor sports for recreational purposes - Birinci, Muhammet Cenk; Yayla, Özgür (Anais Brasileiros de Estudos Turísticos, 2023)
The present study was carried out in the sample of extreme sports centers in Turkey in order to determine the mediating role of recreational service quality in the effect of leisure motivation on leisure satisfaction. In the research, it was determined that recreational service quality has a mediating effect between leisure motivation and leisure satisfaction. The research findings offer suggestions to academicians studying in the context of recreation literature in different activity types and different sample groups.